Development of a 4-DOF haptic micromanipulator utilizing a hybrid parallel-serial flexure mechanism. (April 2018) - Pinskier, Joshua; Shirinzadeh, Bijan; Clark, Leon; Qin, Yanding
Abstract: In the field of micromanipulation, there exists a pressing need for flexible manipulation systems that facilitate the intuitive performance of a range of micro-scale tasks. Parallel or serial chains of compliant flexure mechanisms, driven by piezoelectric actuators (PEAs) are ideal micropositioners for these tasks. They offer smooth, continuous motion with subnanometric accuracy. However, cross-coupling and assembly errors limit their tracking precision when multiple degrees of freedom (DOFs) are used, and current manufacturing techniques limit mechanisms to planar designs. This paper presents a methodology which enables a human operator to precisely control the motion of a multi-DOF piezo-actuated flexure mechanism with haptic feedback. An experimental master-slave manipulator is investigated, consisting of a 4-DOF hybrid parallel-serial slave mechanism. Internal sensors and kinematic information enable the estimation of slave position and orientation. From this, a bilateral haptic controller has been developed to compensate for coupling and assembly errors, and PEA hysteresis nonlinearities present in the slave mechanism. Master mechanism inverse dynamics control is implemented to offset master mechanism inertia, whilst passivity control guarantees stability. Experimental analysis demonstrates precisions of approximately 30 nm can be achieved during low speed interactions, with intuitive environmental force feedback. With appropriate choice of end-effector, the system could be used for tasks such as the assembly of microelectromechanical systems (MEMS).